PRESCHOOL, SCHOOL, AND ADOLESCENT AGE: A COMPREHENSIVE PSYCHO-PEDAGOGICAL ANALYSIS OF PERSONALITY DEVELOPMENT - Takhirzhanova , Rukhshona (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article presents a comprehensive analysis of the features of personality development at the preschool, school, and adolescent stages. The key psychological and pedagogical characteristics of each age period, their interrelation, and continuity are considered. Special attention is given to the role of family, educational environment, and social factors in personality formation. The article aims to identify effective approaches to the upbringing and education of children and adolescents in modern conditions. Particular attention is paid to the problems of children’s adaptation to the school environment, the formation of stable learning motivation, and the development of communication skills. Factors influencing successful socialization of the personality are examined, including family upbringing, pedagogical influence, and the impact of the digital environment. In addition, the article highlights the difficulties of adolescence related to identity crisis, emotional instability, and the search for life orientations. Pedagogical and psychological recommendations are proposed to support adolescents and to form a positive life attitude in them. The practical significance of the study lies in the possibility of using the obtained results in educational practice, in the development of curricula, as well as in the activities of teachers and psychologists working with children and adolescents.